Review Peraturan dan Kebijakan Pemerintah terhadap Pariwisata di Indonesia - Zulfatah Yasin (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2022)
This study aims to analyze tourism regulations and policies as the main sector of the economy using descriptive analysis methods, library research and comparisons of the two countries of Indonesia and Japan. This study uses a comparative study method between Indonesia and Japan. It was found that Indonesia has a "Value chain" in the tourism industry consisting of regulations and policies that support the tourism program and all its stakeholders. Meanwhile, in Japan, it has a lot of local culture that really supports the tourism process.